Is forest research in accord with the strategic challenges of the forest sector? A case study on Finland. - Seppälä, Risto; Saarikko, Jarmo (Commonwealth Forestry Association, 2014)
The purpose of the study was to examine how forest research in Finland is directed and how it should be directed in order to support the development of the forest sector. The classification of research disciplines was based on the international Forest Decimal Classification system. Two variables were used: the number of peer reviewed publications and the number of researchers. The results showed that the strongest disciplines based on the number of publications are ecology and biology representing 42%. As for the number of scientists, silviculture is number one with 24%. The weakest category is research on markets of forest products with the respective shares of 2 and 4%. After all, the real issue in forest research in Finland is not so much an excess or a lack of certain type of research but rather the implementation of existing research results. Nevertheless, more policy-oriented research is needed and more emphasis should be placed on technological and socio-economic aspects. The current dominance of empirical biophysical sciences in forest research is increasingly questioned by funders and other customers. However, there is a danger that an excessive customer orientation leads to short-term thinking and alleviation of basic research.
Keywords: julkaisut; tutkijat; tutkimustoiminta